Inlet gap effect on aerodynamics and tonal noise generation of a voluteless centrifugal fan. (8th December 2022) - Ottersten, M.; Yao, H.D.; Davidson, L.
Highlights: The tonal noise generated from a voluteless centrifugal fan is studied. The noise is predicted by coupling IDDES with FW-H Formulation 1A. Redesigning the gap affects the aerodynamic and acoustic performances with opposite trends. Either narrowing the gap width or elongating the gap length can enhance the turbulence at the entry that develops from the gap. The enhancement of the gap turbulence leads to a reduction in noise generation but worsens the aerodynamic performance in pressure rise. Abstract: In this paper, the gap effects on the aerodynamics and tonal noise generation of voluteless centrifugal fans are studied based on different gap geometries. The study is motivated by the state of the art of this type of fan, for which the tonal noise generation due to the gap turbulence has not been addressed concerning the gap geometry, while a recent study reported that there is tonal noise at the blade passing frequency (BPF) from the gap turbulence. We simulate the configurations using a hybrid method coupling the improved delayed detached eddy simulation (IDDES) with Formulation 1A of Farassat. Our simulation shows regions with high vorticity magnitudes in the channel between two blades near the trailing edges close to the shroud. The turbulence renders a uniform pressure rise. By changing the gap design, the turbulent regions can be reduced. The configurations show a similar trend of the root mean square (RMS) pressure on the blade leading edge (BLE), largest at the shroud, and decays when the distance to the gap increases. The gap designs affect the amplitude of the RMS pressure, which is connected to the BPF. Spectral analysis is performed for the surface pressure fluctuations and the sound pressure upstream of the fan. The surface pressure fluctuations show that, for all cases, the regions with high energy are identical to the locations where the gap turbulence evolves and accounts for the impingement on the BLE. The amplitude of the tonal noise at the BPF differs between the cases.